Comparison of Supine and Prone Methods of Leg Length Inequality Assessment - Cooperstein, Robert (J Chiropr Med, 2017)
OBJECTIVE: The primary objective of the current study was to determine the reliability between methods of supine and prone leg length inequality (LLI) assessment. The secondary objective was to determine if the degree of examiner confidence affected the degree of intermethod agreement. METHODS: Two experienced doctors of chiropractic assessed 43 participants for LLI, one using a prone and the other a supine method. They stated whether they were confident or not confident in their findings. RESULTS: Kappa values for intermethod agreement were 0.16 for the full data set; 0.00 for the n = 20 subgroup with both examiners confident; 0.24 for the n = 18 subgroup with 1 examiner confident; and 0.55 for the n = 5 subgroup with neither examiner confident. Supine and prone measures exhibited slight agreement for the full data set, but no agreement when both examiners were confident. The moderate agreement with both examiners not confident may be an artifact of small sample size. CONCLUSIONS: This study found that supine and prone assessments for leg length inequality were not in agreement. Positioning the patient in the prone position may increase, decrease, reverse, or offset the observed LLI that is seen in the supine position.